MULTI-STAGE REACTION AND SEPARATION SYSTEMS OF A CO2-BASED HYDROMETALLURGICAL PROCESS - ZHAO HUANGJING; ZHOU XIAOZHOU (2021)
The present invention provides a CO2-based hydrometallurgical multi-stage reaction and separation system, which comprises: a raw material pre-washing device configured to continuously input and fully mix industrial solid waste, mineral raw materials and mine tailings with reagents and water at specific ratio; a reactor configured to continuously input slurry with CO2 and continuously discharge the reacted slurry; multi-stage solid-liquid separators configured to perform multi-stage solid-liquid separation on the slurry and recycle unreacted solid particles, obtained by the solid-liquid separation, back into the raw material pre-washing device; a byproduct preparation device configured to generate calcium- and magnesium-based products from filtrate containing target calcium ions and magnesium ions; and a recycling water recirculating device configured to recycle recycling water back to the system. The present invention can implement continuous reaction to maximize throughput, and achieve multi-stage circulating reaction. In addition, the present invention reduces CO2 loss in the process of removing a raw material in a batch reaction. 본원은 공업 폐기물, 광석 원료 또는 폐석, 시약과 물을 일정한 배합비로 연속적으로 투입하여 충분히 혼합시키는 원료 사전 세척 장치; 슬러리가 연속적으로 투입되고, 이산화탄소가 연속적으로 투입되며, 반응을 거친 슬러리를 연속적으로 배출하는 반응장치; 슬러리를 다단 고액분리시키고, 고액분리된 미반응 고체입자를 원료 사전 세척 장치에 순환시키는 다단 고액분리장치; 상청액에 포함되는 목적 칼슘이온과 마그네슘이온을 칼슘 마그네슘 제품으로 제조하는 부생성물 제조장치; 회수수를 시스템으로 환류시키는 회수수 순환 장치;를 포함하는 이산화탄소 기반 습식제련의 다단 반응 및 분리 시스템을 개시한다. 본원은 연속적인 반응을 구현하여 처리량을 최대화시킬 수 있고, 다단 순환 반응도 가능케 할 수 있으며, 또한 회분식 반응에서 원료를 제거하는 과정에서의 이산화탄소 손실을 감소시킨다.